2016
DOI: 10.1002/uog.15913
|View full text |Cite
|
Sign up to set email alerts
|

Prospective first‐trimester screening for trisomies by cell‐free DNA testing of maternal blood in twin pregnancy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 26 publications
6
102
1
1
Order By: Relevance
“…(2018) and excluded it as Ariosa Diagnostics Inc. (San Jose, California) confirmed that NGS was used for DNA quantitation in an unknown proportion of study samples. Fourth, we excluded seven studies (published in eight articles) from this review that, according to information from Ariosa Diagnostics Inc. (San Jose, California), used DNA microarray as DNA quantitation method in an unknown proportion of study samples. These “mixed technology” studies might provide additional useful information on the test accuracy (see Appendix 5).…”
Section: Discussionmentioning
confidence: 99%
“…(2018) and excluded it as Ariosa Diagnostics Inc. (San Jose, California) confirmed that NGS was used for DNA quantitation in an unknown proportion of study samples. Fourth, we excluded seven studies (published in eight articles) from this review that, according to information from Ariosa Diagnostics Inc. (San Jose, California), used DNA microarray as DNA quantitation method in an unknown proportion of study samples. These “mixed technology” studies might provide additional useful information on the test accuracy (see Appendix 5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a policy was proposed that the fetal fraction used to give a successful cell‐free DNA result in dichorionic twin pregnancies should be the lower fetal fraction of the two fetuses and not the total fetal fraction . This would, however, result in an increase in failure rate by three‐fold compared with singleton pregnancies . The performance of screening for trisomic twin pregnancies cannot yet be provided as the numbers are still too small.…”
Section: Screening Using Cell‐free Dna In Maternal Bloodmentioning
confidence: 99%
“…Although its detection rates are lower than those observed for singleton pregnancies, first‐trimester combined screening by nuchal translucency and serum analytes (free β‐human chorionic gonadotropin, pregnancy associated‐plasma protein‐A) has a detection rate for Down syndrome of 70%–72% with a 5% false‐positive rate for twins . Cell‐free DNA screening is also available for twin gestations . The American Congress of Obstetricians and Gynecologists does not recommend the use of cell‐free DNA screening in multiple gestations; however, the American College of Medical Genetics recommends discussing the validity of cell‐free DNA screening with the laboratory before offering the test to women with multiple gestations …”
Section: Chorionicity and Amnionicitymentioning
confidence: 99%
“…Discordant nuchal translucency findings (≥20%) are more concerning in cases of monochorionic twinning and have a 30% risk of early fetal death or TTTS . Cell‐free DNA can also be considered for aneuploidy screening in monochorionic gestations …”
Section: Chorionicity and Amnionicitymentioning
confidence: 99%